Combination of Collagen-Based Scaffold and Bioactive Factors Induces Adipose-Derived Mesenchymal Stem Cells Chondrogenic Differentiation In vitro - Calabrese, Giovanna; Forte, Stefano; Gulino, Rosario; Cefalì, Francesco; Figallo, Elisa; Salvatorelli, Lucia; Maniscalchi, Eugenia T.; Angelico, Giuseppe; Parenti, Rosalba; Gulisano, Massimo; Memeo, Lorenzo; Giuffrida, Raffaella (Frontiers in Physiology, 2017)
Recently, multipotent mesenchymal stem cells (MSCs) have attracted much attention in the field of regenerative medicine due to their ability to give rise to different cell types, including chondrocytes. Damaged articular cartilage repair is one of the most challenging issues for regenerative medicine, due to the intrinsic limited capability of cartilage to heal because of its avascular nature. While surgical approaches like chondral autografts and allografts provide symptoms and function improvement only for a short period, MSC based stimulation therapies, like microfracture surgery or autologous matrix-induced chondrogenesis demonstrate to be more effective. The use of adult chondrocytes, which are the main cellular constituent of cartilage, in medical practice, is indeed limited due to their instability in monolayer culture and difficulty to collect donor tissue (articular and nasal cartilage). The most recent cartilage engineering approaches combine cells, biomaterial scaffold and bioactive factors to promote functional tissue replacements. Many recent evidences demonstrate that scaffolds providing specific microenvironmental conditions can promote MSCs differentiation toward a functional phenotype. In the present work, the chondrogenic potential of a new Collagen I based 3D scaffold has been assessed in vitro, in combination with human adipose-derived MSCs which possess a higher chondrogenic potential compared to MSCs isolated from other tissues. Our data indicate that the scaffold was able to promote the early stages of chondrogenic commitment and that supplementation of specific soluble factors was able to induce the complete differentiation of MSCs in chondrocytes as demonstrated by the appearance of cartilage distinctive markers (Sox 9, Aggrecan, Matrilin-1 and Collagen II), as well as by the cartilage-specific Alcian Blue staining and by the acquisition of typical cellular morphology. Such evidences suggest that the investigated scaffold formulation could be suitable for the production of medical devices that can be beneficial in the field of articular cartilage engineering, thus improving the efficacy and durability of the current therapeutic options.